2005
DOI: 10.1063/1.2146069
|View full text |Cite
|
Sign up to set email alerts
|

Improved stoichiometry and misfit control in perovskite thin film formation at a critical fluence by pulsed laser deposition

Abstract: Pulsed laser deposition (PLD) is a good method for growing high-quality functional oxide thin films because of the technical simplicity and the ease with which deposition can be switched from one material to another. However, the repeatability of film quality is often hard to achieve, especially when using several different PLD systems. Here we report the steps that we have taken to grow nearly bulk-equivalent defect-free thin films, with SrTiO3 as an example, by using PLD in a reproducible fashion. The ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
192
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(208 citation statements)
references
References 7 publications
13
192
1
2
Order By: Relevance
“…PLD growth is very easy and allows, in principle, a quasi-stoichiometric transfer of the target composition to the substrate. On the other hand, it has been shown that even in the case of STO homoepitaxy, the overall stoichiometry, thus the defect density, of PLD grown films is extremely sensitive to the deposition conditions, in particular to the target to substrate distance, oxygen background pressure, heater temperature, laser fluence and laser spot areas [34]. In short, the stoichiometric transfer of ablated species to the substrate depends crucially on the plume dynamics.…”
Section: The Growth Of Laalo 3 /Srtio 3 Interfacesmentioning
confidence: 99%
“…PLD growth is very easy and allows, in principle, a quasi-stoichiometric transfer of the target composition to the substrate. On the other hand, it has been shown that even in the case of STO homoepitaxy, the overall stoichiometry, thus the defect density, of PLD grown films is extremely sensitive to the deposition conditions, in particular to the target to substrate distance, oxygen background pressure, heater temperature, laser fluence and laser spot areas [34]. In short, the stoichiometric transfer of ablated species to the substrate depends crucially on the plume dynamics.…”
Section: The Growth Of Laalo 3 /Srtio 3 Interfacesmentioning
confidence: 99%
“…[16] However, at less than optimal growth conditions, the highly energetic plume-substrate interactions can produce undesirable departures from stoichiometry. [17,18] As summarized in Table 1 of Supporting Information, the PLD growth conditions used in published reports on the LAO/STO interface formation were not uniform, suggesting that the differences in the growth parameters might contribute to inconsistent observations and/or interpretations of interface conductivity. Most importantly, compared to conventional PLD growth conditions for typical perovskite oxides, [19,20] many LAO/STO heterostructures were grown at unusually low P(O 2 ) and rather high temperatures.…”
mentioning
confidence: 99%
“…In particular, STO thin films grown at high laser fluence are Ti rich, whereas thin films grown at low laser fluence are Sr rich. 7,13 By employing positron annihilation lifetime spectroscopy, we explicitly demonstrated that Dc is induced by Sr and Ti vacancies for the high and low fluence regime, respectively. 8 Figure 1 also exemplifies that at a given fluence, e.g., F ¼ 1.5 J/cm 2 , the films can be nearly stoichiometric (D TS ¼ 44 mm) but also extremely non-stoichiometric with a Ti-rich (D TS ¼ 40 mm) or a Sr-rich (D TS ¼ 48 mm) composition, depending on the target-to-substrate distance.…”
mentioning
confidence: 99%
“…However, in Ref. 7, it was demonstrated that the Sr/Ti ratio of homoepitaxially grown STO thin films strongly depends on the laser fluence, and that a stoichiometric transfer is only obtained for a certain laser fluence. The fluence dependence of the cation stoichiometry has also been recently confirmed for a variety of perovskite thin films.…”
mentioning
confidence: 99%